Новое содержание правозащитной функции современного Украинского государства - Аракелян, Минас Рамзесович; Аракелян, Мінас Рамзесович; Arakeljan, Minas (Одеса : Юрид. літ., 2012)
The article discussed the problem of transforming of the content of human rights function of the modern state. Particular attention is paid to the implementation of human rights function of the modern Ukrainian state in the context of the legal reforms that were traversed in the country.
Аракелян M. P. Новое содержание правозащитной функции современного Украинского государства / М. Р. Аракелян // Актуальні проблеми держави і права : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. літ., 2012. – Вип. 67. - С. 32-39.
Keywords: современное государство; функции современного государства; трансформация; правозащитная функция современного государства; защита прав и свобод человека; сучасна держава; функції сучасної держави; трансформація; правозахисна функція сучасної держави; захист прав і свобод людини; modern state; the functions of the modern state; transformation; human rights function of the modern state; the protection of human rights and freedoms